Twenty years of applied experimental research on wood-plastic composites. An Italian case study - Sara Lanzoni; Luca Guardigli; Pietro Pizzardi (Discover Civil Engineering, 2025)
Abstract The article describes the development of a WPC product, and it was possible to explore the topics in depth thanks to the multi-year cooperation between some Universities and an Italian manufacturing company. It summarises, in a critical manner, the activity that led to the optimisation of the product according to a series of criteria such as durability, physical–mechanical characteristics, production costs, processability and reduction of environmental impact. The data collected along the way are numerous, concerning flexural strength, imbibition, durability and real behaviour in relation to the exposure to atmospheric agents, solar radiation and the marine environment, of applications carried out with continuity from the early 2000s to the present day. The analysis of the evolution of the product, both in terms of its material composition and its applications, is conducted through the main steps that led to the variations in the formula of the compound, to the changes in the production process, such as the transition from 'one-step' to 'two-step' production lines, and to important implementations for building and marine industries. The final section of the article deals with possible future research topics to lead to product improvement in response to real technical and market needs. The novelty of this contribution lies in providing a concise view of the product development process in relation to experimental tests and the needs of manufacturers and users.